Correlation Analysis Between the Need for Interactive Ethnographic Bumper Videos and Elementary School Students’ Home Learning Activities - Deden Nur Fatahillah; Aswasulasikin; Makmum Raharjo (JTP - Jurnal Teknologi Pendidikan, 2026)
This study explores the relationship between the need to develop interactive ethnographic bumper videos and home learning processes related to cultural education at the elementary school level. The adopted method was descriptive quantitative, involving 330 students and 12 teachers from three elementary schools in South Sumatra Province. The data collection instruments encompassed six dimensions of needs (pedagogical, technical, cognitive, aesthetic, sociocultural, and evaluative) along with 20 indicators of home learning activities. Data were gathered through surveys, observations, and interviews, and subsequently analyzed using percentage techniques and Spearman correlation analysis. The findings indicate that all dimensions fall within the high to very high category, with a significant correlation between school media needs and home learning activities (rs = 0.70-0.75; p<0.05). The aesthetic (88.1%) and cognitive (86.7%) aspects were identified as top priorities in media development. These results emphasize that interactive ethnographic media play a vital role in integrating formal and nonformal learning experiences and supporting the implementation of collaborative learning that is relevant to local culture. Practically, the findings serve as a foundation for developing digital learning designs grounded in cultural values; theoretically, they reinforce the Cognitive Theory of Multimedia Learning within the field of elementary cultural education.